1998
DOI: 10.1046/j.1529-8817.1998.340477.x
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION, CHARACTERIZATION, AND CHROMOSOME MAPPING OF AN ACTIN GENE FROM THE PRIMITIVE GREEN ALGA, NANNOCHLORIS BACILLARIS (CHLOROPHYCEAE)

Abstract: Historically, the genus Nannochloris has been classified using the morphology of cell division, although the mechanics of division remain relatively poorly understood. Nannochloris bacillaris reproduces by binary fission. Microscopic observation with fluorescein isothiocyanate‐phalloidin showed that actin filaments localized near the nucleus and appeared as a ring‐ or beltlike structure in the septum‐forming area in the middle of the cell during cell division. In primitive unicellular Chlorophyta such as N. ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…Nannochloris bacillaris NRJ was collected from Lake Nakatuna in Nagano Prefecture by Dr. N. Takamura of the National Institute for Environmental Studies at Tsukuba, Japan (Ogawa et al 1995;Arai et al 1998;Yamamoto et al 2001) and was given to us by Prof. K. Ueda of Nara Women's University (NRJ). M. coccoides CCAP251/1B was purchased from CCAP in 1998.…”
Section: Algal Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Nannochloris bacillaris NRJ was collected from Lake Nakatuna in Nagano Prefecture by Dr. N. Takamura of the National Institute for Environmental Studies at Tsukuba, Japan (Ogawa et al 1995;Arai et al 1998;Yamamoto et al 2001) and was given to us by Prof. K. Ueda of Nara Women's University (NRJ). M. coccoides CCAP251/1B was purchased from CCAP in 1998.…”
Section: Algal Culturementioning
confidence: 99%
“…The nucleotide sequences of the actin genes from M. geminata SAG 12.88 and C. lobophora were used for phylogenetic analysis, along with the published sequences from N. bacillaris (Arai et al 1998), M. coccoides CCAP251/1B, N. eucaryotum KSW 0203 (a single colony was isolated from UTEX 2502, Yamamoto et al 2003), N. atomus SAG 14.87, N. sp. SAG 251-2., Picochlorum atomus CCAP251/ 7, P. kessleri IAM C-531 (Yamamoto et al 2001), C. vulgaris IAM C-536, C. sorokiniana IAM C-212, and Trebouxia erici IAM C-593 (Yamamoto et al 2003).…”
Section: Phylogenetic Analysis Of the Actin Gene Sequencesmentioning
confidence: 99%
“…The presence of actin in the cleavage furrow of Chlamydomonas, a member of the Chlorophyceae, suggests that actin provides the generative force for cytokinesis in a manner similar to the contractile-ring microfilaments (Harper et al 1992). In Nannochloris bacillaris Naumann, which belongs to the Trebouxiophyceae along with Chlorella (Yamamoto et al 2001(Yamamoto et al , 2003, Arai et al (1998) showed that actin filaments localize near the nucleus and appear as a belt-like structure in the septum-forming area in the middle of the cell, during cell division. Protoplast division in Chlorella vulgaris seems to involve an actin-based phenomenon, as in other unicellular algae.…”
Section: Protoplast Division In Chlorella Vulgarismentioning
confidence: 99%
“…Pulse field gel electrophoresis (Higashiyama and Yamada 1991, Arai et al 1998, Yamamoto et al 2001) and flow cytometry (Wilhelm et al 1982, Veldhuis et al 1997 have also been utilized (summarized by Kapraun 2007). The genus Nannochloris and related genera include some of the smallest and ultrastructurally simple phototrophic eukaryotes, with genomes as small as 12.6 Mbp (Arai et al 1998, Yamamoto et al 2001.…”
Section: Measurement Of Fluorescence Intensity By Lscmentioning
confidence: 99%
“…The genus Nannochloris and related genera include some of the smallest and ultrastructurally simple phototrophic eukaryotes, with genomes as small as 12.6 Mbp (Arai et al 1998, Yamamoto et al 2001. The genome size of the binary fission type N. bacillaris was estimated as 20.3 Mbp (Arai et al 1998, Yamamoto et al 2001. LSC functions as both a microscope and a flow cytometer, and is thus able to automatically calculate the total level of fluorescence intensity and simultaneously observe the sample shape.…”
Section: Measurement Of Fluorescence Intensity By Lscmentioning
confidence: 99%